NEW RECORD OF BENT-TOED GECKO (CYRTODACTYLUS BOBROVI NGUYEN, LE, PHAM, NGO, HOANG, PHAM & ZIEGLER, 2015) FROM CUC PHUONG NATIONAL PARK - Thanh Tung, Nguyen; Huy Quang, Nguyen; Quang Vinh, Luu (Journal of Forestry Science and Technology, 2018)
The existence of Cyrtodactylus bobrovi is reported for the first time from Thanh Hoa Province, in northern Vietnam, based on morphological characters of one adult female specimen collected in 30th September 2017 on the karst cliff, in the limestone karst forest of Cuc Phuong National Park. Morphological characters of the specimen mostly matched with the original description of Nguyen et al. (2013), such as supralabials 11 - 10; infralabials 11 – 10; 41 longitudinal rows at midbody. Noticeably, the specimen from Cuc Phuong National Park is differentiated from the original description by the presence of precloacal pores in the female (versus absent in females of the paratypes). Besides C. cucphuongensis described in 2011, this discovery increases the total number of species in the genus Cyrtodactylus in Cuc Phuong National Park to two species at present. While the limestone karst forest has been proven to be an ideal habitat for the Cyrtodactylus species, the number of Cyrtodactylus species in Cuc Phuong - with toal area of 22,200 ha, is still likely to be underestimated. Therefore, further research on diversity of reptiles, ecology and threats should be carried out to gain full understanding on the reptilian fauna of the national park and provide effective conservation measures.